Untangling Constructivism, Knowledge, and Knowledge-building for ‘future-oriented’ Teaching - Gilbert, J (The New Zealand Council for Educational Research (NZCER), 2018)
Building on earlier work in Set on “confusion” around the term constructivism in education, this article explores four different meanings of constructivism, looking at their very different origins and purposes. It argues that mixing up these meanings has produced the confusion identified in the earlier article. The article also suggests that constructivism has been pushed to its limits as a framework for thinking about teaching, learning and/or knowledge development in 21st century schools, and another idea is now needed. The article reviews Bereiter and Scardamalia’s ‘knowledge-building’ concept as one possible contender.